Adalimumab. Issue 3 (May 2016) - Brankov, Nikoleta; Jacob, Sharon E.
Abstract : ABSTRACT: A drug is a particular substance in physiology that exerts an effect when ingested or otherwise introduced into the body. Drugs may be administered in a variety of constitutions from capsules, injections, creams, and ointments to inhalants, liquids, and dermal patches. Administration is by way of different routes, namely, topical, parenteral, inhalation, and via injection routes such as subcutaneous, intramuscular, or intravenous. The purpose of this column is to direct the reader's attention to some of the more common drugs used in dermatology. The mechanism of action for the drug, the indications for its use, efficacy, dosing and administration, monitoring guidelines, adverse side effects, and any standard alternatives are discussed. In addition, this column contains pertinent patient education on the use of the medication. This article focuses on a common medication for plaque psoriasis, adalimumab.